Mucoadhesive plasticized system of branched poly(lactic-co-glycolic acid) with aciclovir - Snejdrova, Eva; Drastik, Martin; Dittrich, Milan; Kastner, Petr; Nguyenova, Jana (Drug development and industrial pharmacy, 2016)
Commercially available antibacterial semisolid preparations intended for topical application provide only short-term drug release. A sustained kinetics is possible by exploitation of a biodegradable polymer carrier. The purpose of this work is to formulate a mucoadhesive system with aciclovir (ACV) based on a solid molecular dispersion of this drug in poly(lactic-co-glycolic acid) branched on tripenterythritol (PLGA/T). The ACV incorporation into PLGA/T was carried out either by solvent method, or melting method, or plasticization method using various plasticizers. The drug-polymer miscibility, plasticizer efficiency and content of residual solvent were found out employing DSC. Viscosity was measured at the shear rate range from 0.10 to 10.00 s(-1) at three temperatures and data were analyzed by Newtonian model. The mucoadhesive properties were ascertained in the tensile test on a mucin substrate. The amount of ACV released was carried out in a wash-off dissolution test. The DSC results indicate a transformation of crystalline form of ACV into an amorphous dissolved in branched polyester carrier, and absence of methyl formate residuals in formulation. All the tested plasticizers are efficient at Tg depression and viscosity decrease. The non-conventional ethyl pyruvate possessing supportive anti-inflammatory activity was evaluated as the most suitable plasticizer. The ACV release was strongly dependent on the ethyl pyruvate concentration and lasted from 1 to 10 days. The formulated PLGA/T system with ACV exhibits increased adhesion to mucosal hydrophilic surfaces and prolonged ACV release controllable by degradation process and viscosity parameters.
Keywords: hydrofobní a hydrofilní interakce; Biocompatible Materials; Delayed-Action Preparations; kyselina mléčná; Time Factors; povrchové vlastnosti; kyselina polyglykolová; Lactic Acid; biokompatibilní materiály; velikost částic; Hydrophobic and Hydrophilic Interactions; léky s prodlouženým účinkem; Surface Properties; Acyclovir; změkčovadla; acyklovir; Drug Liberation; časové faktory; uvolňování léčiv; Plasticizers; Polyglycolic Acid; Particle Size